Urban costs, wages, and selection - Wilfried Dalvai (Universität Rostock, Institut für Volkswirtschaftslehre, 2016)
In most countries housing and commuting costs amount for one-third or more of households' budgets. These urban costs have substantial effects on wages and income inequality. Urban costs play an important role for locational and economic decisions of individuals and firms. This paper enriches the topic on urban costs with cornerstones in much recent micro-modeling in international trade and regional and urban economics by analyzing the effects of urban costs and firm heterogeneity with endogenous markups on wages and selection. With increasing commuting technology only more productive and less firms survive. Firms have higher costs because they have to pay higher wages to compensate workers for the higher urban costs. Despite higher wages welfare decreases with larger urban costs because consumer surplus decreases an there are larger expenses for housing and commuting. Wage premia are hump-shaped with respect to urban costs.
Keywords: F12; R12; E24; 330; urban costs; heterogenous firms; wages; selection; college wage premium; inequality